Normal Canine Prostate Gland: Repeatability, Reproducibility, Observer‐Dependent Variability of Ultrasonographic Measurements of the Prostate in Healthy Intact Beagles. (7th January 2013) - Leroy, C.; Conchou, F.; Layssol‐Lamour, C.; Deviers, A.; Sautet, J.; Concordet, D.; Mogicato, G.
Summary: Most prostatic diseases in dogs are associated with prostatomegaly, and transabdominal ultrasonography has become the imaging modality of choice for evaluation of the prostate gland in the dog. The aim of the present study was to assess the reproducibility, the repeatability and interobserver variations of sonographic measurements of prostate and to determine which measurement had the lowest variability. Length and height of prostate gland were measured on longitudinal views, width of the prostate gland and height of left and right lobes of the gland on transversal views. The within‐day and between‐day variabilities of the prostatic parameters were determined by performing 1350 (270 length, 270 height, 270 width, 270 height of right lobe and 270 height of left lobe) examinations on ten healthy intact beagle dogs on six different days, in a two‐week period (three days for the five dogs, three different days for the five others). Three observers with different levels of experience in ultrasonography performed the examinations. The lowest within‐day and between‐day standard deviation and coefficient of variation values were observed for the width of the prostate. The width of the gland measured on transverse frozen images seems to be the most reliable measurement for evaluating size of prostate glands in healthy dogs, although the shape, position, outline, and echogenicity of the prostate should also be assessed.